2007
DOI: 10.1007/s00595-007-3504-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Small Cell Carcinoma Successfully Treated by Surgery and Postoperative Chemotherapy Consisting of Cisplatin and S-1: Report of a Case

Abstract: We herein report a case of gastric small cell carcinoma (GSCC), which was successfully treated by surgery and postoperative chemotherapy consisting of cisplatin (CDDP) and the fluoropyrimidine S-1. The patient was a 63-year-old man in whom a gastric tumor had been endoscopically detected. The type 1 tumor was located in the gastric body. An abdominal computed tomogram showed many metastasized nodes around the stomach. A total gastrectomy with regional node dissection was performed. The removed tumor was histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…However, we found no survival benefit of adjuvant chemotherapy for advanced gastric EC. Recently, some authors have reported successfully treating cases of gastric EC with different combination chemotherapies, such as etoposide/CDDP, CPT-11/CDDP, and S-1/CDDP [19,22,[24][25][26][27][28]. However, at present there is no standard chemotherapy regimen for advanced gastric EC.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no survival benefit of adjuvant chemotherapy for advanced gastric EC. Recently, some authors have reported successfully treating cases of gastric EC with different combination chemotherapies, such as etoposide/CDDP, CPT-11/CDDP, and S-1/CDDP [19,22,[24][25][26][27][28]. However, at present there is no standard chemotherapy regimen for advanced gastric EC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, few studies have reported favorable results with a combined treatment modality of surgery followed by chemotherapy in resectable cases of GSCC, which are similar to that for conventional gastric cancer 2,9,10,11) . On the other hand, in unresectable cases, chemotherapy showed efficacy for GSCC 3,12,13,14,15) .…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, in unresectable cases, chemotherapy showed efficacy for GSCC 3,12,13,14,15) . Among the various regimens of chemotherapy reported, cisplatin has been frequently mentioned in the literature 2,3,9,10,11,12,14,15,16) . It remains unclear whether chemotherapy should be given before or after surgery; however, it may be essential in the treatment of GSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A response rate of 41.5% [9] and median sur vival range of 10.4 mo have been reported [10] . In another report, four of 11 patients with endocrine cell carcinomas who were treated with S-1 survived for over 2 years after surgery [11,12] .…”
Section: Issnmentioning
confidence: 99%